Consumer behaviour towards own label: monitoring the Greek experience - Zotos, Yorgos; Boutsouki, Christina; Masouti, Zafeiria (My University, 2008)
In Greece, the traditional perceptions of private label were once of low quality, unbranded alternatives, attracting the most cost-conscious consumers. In today’s private label market, however, a different level of products has emerged – the premium “branded” private label product. Based on a consumer survey conducted in Greece, the current study discusses consumer’s attitude and satisfaction with respect to private label products. Frequency of purchase and consumer characteristics are also discussed in light of empirical evidence.
Keywords: Private label; Consumer attitude; Greece; Food retailing